Lesões de pele em recém-nascidos na unidade de terapia intensiva neonatal - Fontenele, Fernanda Cavalcante (2008)
Infants in the Neonatal Intensive Care Unit (NICU) often get skin lesions on account of the many stressful procedures they are exposed to. This prospective, quantitative and descriptive study was carried out at a public health facility in Fortaleza (Northeastern Brazil) from March to May 2007, in order to investigate skin lesion patterns in infants in the NICU setting. The study population consisted of 137 hospitalized infants. Informed written consent was obtained from the infants’ caretakers. The data collection instrument registered skin lesions through direct observation during bathing, change of diapers, catheters and eye patches and during removal of semi-permeable membranes, elastic adhesive bandages and/or micropores, electrodes and hydrocolloid dressings applied to the skin during punction, among other procedures. Eighty percent of the infants were premature, 63% were male, 61% were caesarean births, 40% presented first-minute apgar scores of 7-10, 49% were diagnosed with moderate prematurity, 74% were full-term, 39% had low birth weight and 44% measured 41–47cm. Thirty-six infants had skin lesions (total 51 lesions) in the form of bruises (46%), erythema (18%), excoriation (12%), ecchymosis (10), pustulas (6%), scaling (4%), myelomeningocele (2%) or gastroschisis (2%). The lesions were inflicted while the infants were being treated with intravenous hydration (84%), antibiotics (78%), mechanical ventilation (53%), phototherapy (33%), parenteral nutrition (27%), blood transfusion (8%), oxygen hood (8%), nasal cpap (6%) or circulating oxygen (4%), or were in a heated incubator (86%), transport incubator (10%) or heated crib (4%). Lesions were observed most often on limbs (52%), torso (24%), head (16%) and other sites (8%). The causes identified were arterial puncture (32%), leaking (14%), contact dermatitis (14%), vein puncture (8%), impetigo (4%), undetermined (4%), congenital malformation (4%), removal of the caul (4%), removal of adhesive bandage (4%), skin dryness (4%), infection (2%), removal of hypoallergenic tape (2%) and birth traumatism (2%). Forty percent of lesions measured < 1cm2 and 68% measured 1-2cm. Most were well defined (38%) and/or localized (92%). Infants with lesions presented prematurity (92%), syndrome of respiratory distress (43%), asphyxia (24%), full-term delivery (8%); risk of infection (6%), risk of hypoglycemia (6%), gastroschisis (2%) or myelomeningocele (2%). Most (47%) weighed 550-999g at birth, with lesions occurring at 455-999g in 47%. Most were newborn (84%) and lesions appeared before the seventh day of life in 47% of cases. Among the parameters lesion type, diagnosis, PN, IG and prematurity, only the latter presented a statistically significant association (p=0.496, by the Fisher-Freeman-Halton test). The study shows the importance of providing the newborn with good-quality holistic nursing care with a view to the special needs of this patient population.